A contribution for integrating dispatching and covering in the emergency vehicles management services. (1st January 2013) - Ibri, Sarah; Nourelfath, Mustapha; Drias, Habiba
In the vehicle management systems, two important issues have to be considered by managers: the dispatching problem with the aim of minimising the response time for current emergency calls; and the covering problem with the objective of keeping proper coverage to satisfy future calls in best times. The purpose of this paper is to investigate the value, in terms of service quality, of integrating the dispatching and covering problems in the same model. A heuristic algorithm, combining ant optimisation and tabu search is used as a solution approach and is included in a discrete event simulator that simulate the working of the system in real time. Several numerical examples are used to compare the integrated approach and the non-integrated one.